2022
DOI: 10.1212/wnl.0000000000013077
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and Clinical Relevance of Enlarged Perivascular Spaces in the Aging Brain

Abstract: Perivascular spaces (PVS) are fluid filled compartments that are part of the cerebral blood vessel wall and represent the conduit for fluid transport in and out of the brain. PVS are considered pathologic when sufficiently enlarged to be visible on magnetic resonance imaging. Recent studies have demonstrated that enlarged PVS (ePVS) may have clinical consequences related to cognition. Emerging literature points to arterial stiffening and abnormal protein aggregation in vessel walls as two possible mechanisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
51
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 60 publications
3
51
0
3
Order By: Relevance
“…Although cSS has not been found in CADASIL (Wollenweber et al, 2017), SVD scores including ePVS and cSS have been reported to influence neuropsychological tests in memory clinic patients (Matsuda et al, 2021). Moreover, the ePVS burden has also been associated with cognitive impairment (Bown et al, 2021). Moreover, other MRI markers for SVD remain uncertain and may provide additional data in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although cSS has not been found in CADASIL (Wollenweber et al, 2017), SVD scores including ePVS and cSS have been reported to influence neuropsychological tests in memory clinic patients (Matsuda et al, 2021). Moreover, the ePVS burden has also been associated with cognitive impairment (Bown et al, 2021). Moreover, other MRI markers for SVD remain uncertain and may provide additional data in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few studies have investigated brain CSVD markers (e.g., WMH and cerebral microbleeds) in relation to delirium ( Omiya et al, 2015 ; Nitchingham et al, 2018 ; Lachmann et al, 2019 ; Clancy et al, 2021 ; Pendlebury et al, 2022 ), no previous study has yet explored the link between MRI-visible PVS and delirium. PVS is frequently seen in the aging brain ( Bown et al, 2022 ) and has been proposed as a key contributor to cognitive decline and dementia in older adults ( Debette et al, 2019 ; Paradise et al, 2021 ). It has been reported that PVS could affect specific cognitive domains, and a negative association of PVS burden with nonverbal reasoning and visuospatial ability has been observed ( Maclullich et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal protein aggregation (e.g., β-amyloid) can block the upstream within the cortical arteries and impair the external drainage of interstitial fluid in the deep white matter, thus contributing to the retrograde enlargement of PVS in CS ( Gouveia-Freitas and Bastos-Leite, 2021 ), and the relationship between β-amyloid accumulation and CS-PVS has been demonstrated in previous studies ( Roher et al, 2003 ; Charidimou et al, 2015 ). Furthermore, the impaired perivascular pathway may cause a vicious feed-forward cycle, further prompting PVS dysfunction and β-amyloid deposition in the vascular wall and brain ( Gouveia-Freitas and Bastos-Leite, 2021 ; Bown et al, 2022 ), which may exacerbate neurovascular dysfunction, neuroinflammation, and neurodegeneration ( Carrano et al, 2012 ; Parodi-Rullan et al, 2021 ), making the brain vulnerable to delirium ( Idland et al, 2017 ; Maldonado, 2018 ; Chan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, MRI-visible PVS may become an indicator of how brain health is affected by poorly controlled risk factors, such as hypertension and sleep deprivation. A further clinically relevant, and likely related, aspect is the increased risk of dementia in individuals with MRI-visible PVS, 1 although their exact relationship with cognitive performance remains a debated topic. 2 Remaining questions include whether MRI-visible PVS themselves lead to disruption of brain tissue and thus increased risk of cognitive impairment, or whether they are merely a marker of an underlying condition such as hypertension or CAA, which is driving the association.…”
mentioning
confidence: 99%
“…More recently, a third model has been put forward, suggesting there is no unidirectional flow, but that interstitial fluid mixes with CSF at the pial surface of the brain, thereby facilitating waste removal. 3 Although this model was not discussed by Brown et al, 1 it may provide an attractive alternative that could potentially reconcile contradicting results that may have arisen due to experimental heterogeneity between laboratories. Of note, these models have largely been established by observations in rodent models, relying on the injection of various tracers into the brain to track their clearance routes.…”
mentioning
confidence: 99%